2016
DOI: 10.1016/j.drugalcdep.2015.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine withdrawal alters the reward omission effect and enhances traits of negative urgency in rats across multiple days of testing

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Background The personality trait of negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In contrast to the above noted decreases in expression linked (mainly) to voluntary cocaine intake, the increases observed in tegmental CB1 receptor expression seem to be a pharmacological effect of cocaine delivery. It should also be noted that cocaine delivery in self-administering rats and yoked drug controls are linked with a conditioned stimulus, and the ventral tegmental area plays a significant role in learning and habit formation (Barker and Rebec 2016 ). In fact, Wang et al ( 2015 ) recently demonstrated the control of tegmental CB1 receptors over cocaine-induced synaptic plasticity and associative learning (Wang et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above noted decreases in expression linked (mainly) to voluntary cocaine intake, the increases observed in tegmental CB1 receptor expression seem to be a pharmacological effect of cocaine delivery. It should also be noted that cocaine delivery in self-administering rats and yoked drug controls are linked with a conditioned stimulus, and the ventral tegmental area plays a significant role in learning and habit formation (Barker and Rebec 2016 ). In fact, Wang et al ( 2015 ) recently demonstrated the control of tegmental CB1 receptors over cocaine-induced synaptic plasticity and associative learning (Wang et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies investigating negative urgency in animals are sparse. One proposed method for generating negative urgency (utilized in both animal and human models) involves unexpected reward omission (5658). In one study, humans or rats were trained to perform an operant task (button pressing or lever pressing, respectively) and were rewarded with either money or a food pellet, respectively (56).…”
Section: Animal Models Of Negative Urgencymentioning
confidence: 99%
“…In this study, higher polygenic 5HT scores (indicating lower 5HT function) were positively correlated with higher self-reported negative urgency and greater levels of alcohol consumption. At this time, there are no preclinical investigations evaluating the relationship between these transmitter systems, alcohol overconsumption, and negative urgency, although one study did report an increase in negative affect during cocaine withdrawal in rats in the reward omission task (58).…”
Section: Neural and Genetic Correlates Of Negative Urgency And Potentmentioning
confidence: 99%